Pengaruh Kecerdasan Emosional terhadap Kemandirian Belajar Siswa pada Mata Pelajaran IPS Kelas VIII SMP Negeri 6 Kota Solok - Rahmadhani, Putri; Basyirun, Fajri; Ikhwan, Ikhwan (Lembaga Yasin AlSys, 2025)
Emotional intelligence is a critical student capability that supports the learning process by enabling individuals to recognize, understand, and manage their emotions effectively. This study aims to examine the influence of emotional intelligence on students’ learning independence in Social Studies (IPS) among Grade VIII students at SMP Negeri 6 Kota Solok. A quantitative approach with a survey method was employed. The population consisted of all Grade VIII students in the 2023/2024 academic year, totaling 122 individuals, with a sample of 94 students selected using proportional random sampling. Data were analyzed using simple linear regression. The results indicate that emotional intelligence has a positive and significant effect on learning independence, as evidenced by a calculated t-value of 8.141, which exceeds the critical t-value of 1.661 at a 0.05 significance level. Emotional intelligence accounts for 41.9% of the variance in learning independence. These findings suggest that higher levels of emotional intelligence are associated with greater learning independence among students. Therefore, fostering emotional intelligence should be an integral component of educational strategies aimed at enhancing students’ academic autonomy.